ASSOCIATION RULE MINING UNTUK PROMO WHATSAPP BLAST PADA PRODUK ACE HARDWARE JAMBI PRIMA MALL: Database;Data Mining;Association Rule;Apriori;PHP;Weka;phpMyAdmin - Puspitorini, Sukma; Wahyuning Astuti, Reny; Jannah Vemi Putri, Miftahul (JURNAL AKADEMIKA, 2022)
Customer service staff at the Ace Hardware Jambi Prima Mall company with one of their jobs is to manage customer databases that are used for marketing strategies, one of which is whatsapp blast, but the customer database is not widely managed, therefore the purpose of this data mining analysis thesis report is to use association rules on the method a priori to describe promos addressed to customers based on shopping history. Association rules were formed with the help of the weka tools through a case study of promotional facilities at Ace Hardware Jambi Prima Mall, the development of this website application using the PHP programming language and the phpMyAdmin database. Weka tools are used for the process of finding the best association rules from training data or customer transaction data and the website application is used to display promo predictions from the results of association rules on weka tools. The inputs needed in this application are customer data, transaction data, product data and promo data with a promo prediction process and whatsapp blast status. From the input and the previous process, it will generate reports or customer outputs who will get promos based on shopping history.